Interactive learning materials contribution for student's engagement in e-learning of mathematics contests: a case study during the Covid-19 pandemic - Paula Lopes, Ana (2022)
The purpose of this paper is to investigate the impact of the use of interactive e-learning materials for students’ engagement in a Mathematics course, concerning the shift from face-to-face classes to online and virtual learning systems, during the COVID-19 outbreak and the lockdown in one of the schools of the Porto Polytechnic. On March 16, 2020, Portuguese Government ordered the closure of all educational institutions, due to the ongoing outbreak of coronavirus disease (COVID-19). Faced with this problem, since students and educators could not be physically present in a traditional classroom environment, two alternatives were “on the table”: suspending courses to reopen them later, when the pandemic “ended”, creating major disruptions in traditional educational calendars, or developing new strategies for the courses to continue, trying to maintain almost all planned educational activities through the use of information and communication technologies, in a distance teaching/learning basis. Our Institution, after analyzing the pros and cons, decided to choose the second alternative. So, in such a short time and without any kind of groundwork or anticipated planning, our traditional ways of learning and teaching were drastically changed. With no further notice, teachers were compelled to adopt remote teaching strategies and to develop synchronous and asynchronous courses. Therefore, using all kind of distance learning strategies, students have been able to continue with their studies, concluding the academic year without ever returning to on-site teaching. However, the efforts did not come without problems: slow or even no Internet connections, no or inadequate devices or technical support, lack of digital proficiency from all educational actors are just some of the challenges faced. On a positive side, extraordinary opportunities must be recognized in the form of innovations and digitalization of the current practices. The opinions of the participants of the study will help demonstrate what may be considered as best practices and problem solving through the use of interactive e-learning materials in times of crisis. Keywords: Innovation, Technology, Interactive Learning Materials, Higher Education, Online Learning, Distance Learning, COVID-19.